Rheological behavior and texture of corn starch gels (Zea mays), arrowroot (Maranta arundinaceaea L.) and cassava (Manihote sculenta Crantz) (Research, Society and Development, 2020)
The main energy reserve in plants is starch. It is unique among polysaccarides for being in the form of granules. Starch granules are heterogeneous mixtures of amylose and amylopectin. Gelatinization and retrogradation of starch depend on the ratio of amylose to amylopectin, type of crystallinity, along with the sizes and structure of starch granules. The present work determined the rheological behavior in a dynamic state, in terms of sweeping frequency, time and temperature, in addition to the extrusion of corn starch gels and arrowroot and cassava starches. The rheological study demonstrated that in all samples analyzed, whether in a non-gelatinized liquid mixture or in the form of gels, behaved as non-Newtonian fluids independent of time. Non-gelatinized mixtures showed properties of dilating non-Newtonian fluids and the gels of pseudoplastic non-Newtonian fluids. Gels were classified as elastic, as it was found that the storage module is larger than the dissipation module with the storage module decreasing with increasing temperature, and thus temperature dependent. With increased temperature, the gels showed low stability which is characteristic of weak gels. The more elastic the gel, the greater its resistance and the corn starch gel was the most resistant when compared to arrowroot and cassava starch.